The role of the affect heuristic and cancer anxiety in responding to negative information about medical tests. Issue 2 (1st February 2018) - Scherer, Laura D.; Shaffer, Victoria A.; Caverly, Tanner; Scherer, Aaron M.; Zikmund-Fisher, Brian J.; Kullgren, Jeffrey T.; Fagerlin, Angela
Abstract : Objective: Little is known about the affective implications of communicating negative information about medical tests. This research explored how affective processes – particularly the Affect Heuristic and cancer anxiety – influence the way in which people respond to such information. Design: Participants received different types of information about PSA screening for prostate cancer and magnetic resonance imaging (MRI) scans for migraine headaches. This was a 2 (Test harm information: present vs. absent) × 2 (Test benefit information: present vs. absent) × 2 (Test recommendation: present vs. absent) between-participants design. Outcome Measures: Perceived risk, perceived benefit and general attitudes towards PSA and MRI testing, cancer anxiety, preferences to receive the tests vs. not. Results: As predicted by the Affect Heuristic, test harm information reduced perceived test benefits. However, information about uncertain test benefit did not increase perceived test risks. Information about the test reduced cancer anxiety, indicating defensive coping. These variables – affect, anxiety, perceived risks and benefits – all uniquely predicted test preferences. Conclusion: Affective processes play an important role in how people respond to and interpret negative information about medical tests. Information about harms and information about the lack of benefit can both make a test seem less beneficial, and will reduce cancer anxiety as a result.